Subduction versus non‐subduction origin of the Nagaland‐Manipur Ophiolites along the Indo‐Myanmar Orogenic Belt, northeast India: Fact and fallacy. (2nd November 2020) - Khogenkumar, Shoraisam; Singh, Athokpam Krishnakanta; Kumar, Santosh; Lakhan, Nongmaithem; Chaubey, Monika; Imtisunep, Sashimeren; Dutt, Amrita; Oinam, Govind
Abstract : The Nagaland‐Manipur Ophiolites (NMO) in northeast India is known for its complex geological history. Tough terrain, thick vegetation, and dismembered exposure of ophiolitic suite of rocks in the region made uneasy for geological investigation and put it in a deadlock for a long time. Only in the last decade has seen an appreciable amount of publications but the results boil down to a hot debate between two opposite schools of thoughts of subduction origin versus non‐subduction origin of the NMO. In this article, we revisit the literature data and compare it with our new geochemical data with an attempt to provide fresh insight into the long‐standing debate on the geodynamic evolution of the NMO. Our investigation arrives at the conclusion that the NMO as a whole cannot be considered as 100% subduction or 100% non‐subduction origin. It is indeed a combination of both. The non‐subduction group of mafic rocks shows a high ratio of incompatible elements (Nb/Yb >1), high‐Ti, enriched LILE, and HFSE with primitive mantle normalized values >5. Their bulk‐rock geochemical composition is equivalent to mid‐ocean ridge basalt (MORB) and ocean island basalt (OIB). The subduction group of rocks, on the other hand, shows a low ratio of incompatible elements (Nb/Yb <1), low‐Ti, depleted LILE, and HFSE with primitive mantle normalized values <1, affinity to the fore‐arc depleted N‐MORB type. Similarly, spinels present in subduction‐influenced mantle rocks show high chromium content (Cr# >50) but it is lower (Cr# <50) in non‐subduction abyssal peridotites of the NMO. Such geochemical variations cannot simply be explained by fractional crystallization or variable degree of partial melting of a single source, but rather signifies derivation from different tectonic settings of subduction and non‐subduction magma factories. We further conclude that the primary compressional force of India‐Myanmar Plate collision and secondary strike‐slip faults running along this ophiolite belt jeopardized the accretionary process which led to distortion and dismembering of the rocks like a scrambled bread. Abstract : Nagaland‐Manipur Ophiolites of northeast India is a unique ophiolite section, which tends to preserve two sets of a genetically different magmatic suite of rocks: (a) Non‐subduction (anhydrous, mid‐ocean ridge + plume type). (b) Subduction Group (hydrous, supra‐subduction zone‐type), which were formed at different time scales. They were formed due to multiple stages of magmatic episodes over a wide range of geological timescale; starting from east Gondwana separation (Late Jurassic‐Early Cretaceous) to the eastward subduction of Indian Plate under Myanmar Plate at Late Cretaceous.